IMPROVING STUDENTS’ READING COMPREHENSION THROUGH COOPERATIVE INTEGRATED AND READING COMPOSITION ON NARRATIVE TEXT - Renaldo, Matheus Ferry; Nurani, Lia Nurani (IKIP Siliwangi, 2020)
This study is revealed based on the observation on the tenth grade of SMKN 3 Cimahi. The subjects of this study consisted of 34 students. The purpose of this study was to improve the students’ reading comprehension using Cooperative Integrated and Reading Composition Method. The research design was Classroom Action Research (CAR) which following Arikunto model. It is used to obtain the results of qualitative data using two cycles described through planning, implementing, observation, and reflection on each cycle. The result of the study showed that there was a development on the students’ reading comprehension. It could be seen from the result of the test. The Minimum Mastery Criterion (KKM) of English lesson was 70 (seventy). The students mean score in the first test was 50, in the first post test the mean score was 65, and in the second post test the mean score was 85. In addition there were 3 students (8.8%) who passed KKM on pre test. In the first pretest there were 9 students (29.41%) who passed KKM. In the second pretest there were 31 students (91.18%) who passed KKM. Then, from the result of observation and interview it showed the positive responses from the students. The students can be more active and improve their ideas. The researchers conclude that Cooperative Integrated and Reading Composition method could improve students’ reading comprehension. Keywords: Reading Comprehension, Cooperative Integrated and Reading Composition, Narrative Text, CAR